Kegiatan Ilmu Pengetahuan Berasaskan Islam di Johor dalam Era Imperialisme British, 1914-1941: Islamic Knowledge-Based Activities in Johor in the Era of British Imperialism between 1914 to 1941 - Ismail, Noorilham; Abdul Rahman, Zulkanain; Mohamed Ariffin, Nur Dayana; Hussain, Norasmahani (Journal of Al-Tamaddun, 2024)
The discussion in this paper focuses on Islamic knowledge-based activities in Johor from 1914 to 1941, during British imperialism. The objective of this paper is to demonstrate that knowledge activities in Johor are still ongoing due to the presence of Islamic-based educational institutions and the availability of authoritative scientific materials for the community at that time. This point is highlighted because throughout the period of British imperialism in Johor, there were things that threatened the position of Islam such as the spread of Christianity as well as issues related to social problems. This article covers the period between 1914, when the British General Counsel was accepted in Johor, and 1941, right before the Pacific War began. Efforts to intensify the knowledge activities were done in a structured manner among the Malay rulers, Islamic religious leaders, and the efforts of individuals in society. Research on documents from selected archives was made using qualitative methods through the analysis of certain documents. The documents were retrieved from the National Archives of Malaysia in Kuala Lumpur and the National Archives of Malaysia Johor Branch. The documents were analyzed to create a systematic and instructive debate based on the discipline of history. In addition, secondary scholarly sources such as journal articles, books, and theses were used to complement the narrative of the discussion. The research concludes that the presence of Islamic-related educational institutions, as well as the availability of authoritative scientific materials, strengthened knowledge activities in Johor despite the British expansion of imperialism policy.